Prevalence of Anxiety and its Relationship with Associated Factors among the Medical Students of Isra University Hyderabad - Nudrat Zeba, Hussain Bux Kolachi, Suhail Ahmed Bijarani , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To evaluate the frequency of anxiety and its relationship with study hours, sleeping hours and mobile phone use among medical students of Isra University Hyderabad. Study Design: Cross-sectional study. Place & Duration: Department of Community Medicine, Isra University from 1 'January to 31' July 2014. Material and Methods: A sample of 106 students was selected through convenient sampling according to well delineated inclusion and exclusion criteria. Questionnaire was designed, pretested and filled by Medical students of 3rd year MBBS. Verbal consent was obtained before filling the questionnaire. The study was approved by the ethical review committee of the institute. Data was analyzed on SPSS-21using descriptive statistics and a p value of< 0.05 was taken statistically significant. Results: Among 106 students, 57(54%) were female. The majority of students were 32(30%) in the age group of 22 years. There was no student without anxiety and all of 106 students showed mild to severe type of anxiety. The use of mobile phone by students, from 1-5 hours was more frequent in 42 students. 6 hours sleeping time was noted in 22 students. In 5 students, duration of study was 11 to 13 hours. There were 89 students who mentioned their performance satisfactory. Conclusion: Excessive use of mobile phone, long hours of sleeping and stress are the factors for high anxiety level among medical students.